Teacher professional development case studies K12, TVET, and tertiary education. (Asian Development Bank, 2021)
Quality teaching is vital to meet the increasingly complex needs of students as they prepare for further education and work in the 21st century. The publication showcases 14 case studies from around the world as examples of teacher professional development programs that support, improve, and harness teaching capabilities and expertise. It also discusses government initiatives and other factors that can contribute to quality teaching.